The Effect of Online Sales on the Income of Betta (Betta splendens) Farmers in Pekanbaru City, Riau Province - Rina Anjani; Eni Yulinda; Darwis AN (Faculty of Fisheries and Marine, Universitas Riau, 2023)
This study aims to analyze the effect of online sales on the income of Betta (Betta splendens) farmers in Pekanbaru City. This study was conducted in June in Pekanbaru City, Riau Province. The method used in this study is a survey method, while the determination of respondents is carried out by a census. The data was collected by direct observations, interviews, and documentation with 38 people of Betta farmers. The results showed that there is a significant influence between online sales on the income of Betta farmers with an R square result of 96.9% with a count of 33.700 ≥ a t-table value of 2.028 with a significant value of 0.000 < 0. 05 then it can be concluded that H0 is rejected and H1 is accepted that the online sales variable (X) has a positive and significant effect on the income of Betta farmers in Pekanbaru City, Riau Province. These results indicate that selling online is better because it can increase the income of fish farmers